To solve the expression \((−4) ×(7/5) ×(−3/4)÷(7/15)\), we can break it down step by step.
-
Multiply the first two terms: \[ (−4) × (7/5) = -\frac{28}{5} \]
-
Now, multiply by \(-3/4\): \[ \left(-\frac{28}{5}\right) × \left(-\frac{3}{4}\right) = \frac{28 \times 3}{5 \times 4} = \frac{84}{20} = \frac{21}{5} \]
-
Now, divide by \((7/15)\): To divide by a fraction, we multiply by its reciprocal: \[ \frac{21}{5} ÷ \left(\frac{7}{15}\right) = \frac{21}{5} × \left(\frac{15}{7}\right) \]
-
Multiply the fractions: \[ \frac{21 × 15}{5 × 7} = \frac{315}{35} = 9 \]
So the final result is \(9\).
The correct response is: 9